Original paperAntiphospholipid antibodies in localized scleroderma: the potential role of screening tests for the detection of antiphospholipid syndrome - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia; Arasiewicz, Hubert; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: The presence of antiphospholipid antibodies (aPL) is associated with infections, drugs and autoimmune disorders. Those antibodies are also detected in approximately 5–20% of the healthy population. The presence of aPL can lead to the occurrence of thrombotic events or abortion, which define the antiphospholipid syndrome (APS). Aim: To evaluate the potential role of aPL in diagnosing APS in patients with localized scleroderma (LoS). Material and methods: Serum samples from 45 patients with various forms of LoS were examined. They were screened with the commercially-available immunodot assay Anti-Phospholipid 10 Dot (GA Generic Assays GmbH, Dahlewitz, Germany). A number of clinical and laboratory parameters, especially APS symptoms, were assessed in patients with positive aPL: arterial and venous thrombotic events, obstetric complications, thrombocytopenia and neurological symptoms. Results : The following profile of aPL IgG or IgM was obtained from patients with LoS: cardiolipin 15/45, phosphatidic acid 41/45, phosphatidyl-choline 0/45, -ethanolamine 6/45, -glycerole 1/45 (patient with Lyme disease), -inositol 7/45, -serine 14/45, annexin V 34/45, 2GPI 21/45, prothrombin 30/45. Antiphospholipid antibodies profile screening in these individuals revealed two cases of suspected secondary laboratory APS. However, no such clinical and laboratory parameters were found in other LoS patients with positive aPL. Similarly, no association was found between the presence of aPL and either thrombotic events or other APS symptoms. Conclusions : Antiphospholipid antibodies are commonly found in patients with LoS but the exact role of these antibodies remains unclear. Clinical manifestations of APS are not frequently seen during LoS.